The spectrum of kidney biopsies in hospitalized patients with COVID-19, acute kidney injury and/or proteinuria. Issue 7 (12th February 2021) - Ferlicot, Sophie; Jamme, Matthieu; Gaillard, François; Oniszczuk, Julie; Couturier, Aymeric; May, Olivia; Grünenwald, Anne; Sannier, Aurélie; Moktefi, Anissa; Le Monnier, Ophélie; Petit-Hoang, Camille; Maroun, Nadine; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) may be associated with kidney injury, which may impact patient's prognosis. Methods: We report a multicentric retrospective case series of patients with COVID-19 who developed acute kidney injury (AKI) and/or proteinuria and underwent a kidney biopsy in Paris and its metropolitan area. Results: Forty-seven patients (80.9% men) with COVID-19 who underwent a kidney biopsy between 8 March and 19 May 2020 were included. The median age was 63 years (interquartile range 52–69). Comorbidities included hypertension (66.0%), diabetes mellitus (27.7%), obesity (27.7%), history of chronic kidney disease (25.5%), cardiac diseases (38.6%) and respiratory diseases (27.3%). Initial symptoms were fever (85.1%), cough (63.8%), shortness of breath (55.3%) and diarrhoea (23.4%). Almost all patients developed AKI (97.9%) and 63.8% required renal replacement therapy. Kidney biopsy showed two main histopathological patterns, including acute tubular injury in 20 (42.6%) patients, and glomerular injury consisting of collapsing glomerulopathy (CG) and focal segmental glomerulosclerosis in 17 (36.2%) patients. Two (4.3%) patients had acute vascular nephropathy, while 8 (17%) had an alternative diagnosis most likely unrelated to COVID-19. Acute tubular injury occurred almost invariably in the setting of severe forms of COVID-19, whereas patients with glomerular injury had various profiles of COVID-19 severity and CG was only observed in patients harbouring a combination of APOL1 risk variants. At the last follow-up, 16 of the 30 patients who initially required dialysis were still on dialysis, and 9 had died. Conclusions: This study describes the spectrum of kidney lesions in patients with COVID-19. While acute tubular injury is correlated with COVID-19 severity, the pattern of glomerular injury is intimately associated with the expression of APOL1 risk variants.